Methods for measuring patient preferences: an update and future directions. Issue 2 (March 2019) - Meara, Alexa; Crossnohere, Norah L.; Bridges, John F.P.
Abstract : Purpose of review: The current review highlights the growing number of available methods used to measure patient preferences and discusses how this impacts preference research in rheumatology. Spurred by the growing role of preferences in regulatory decisions and drug development, researchers have begun applying preference methods to study questions beyond the clinical context. We explore these trends, provide case studies highlighting changes in measuring patient preferences, compare strengths and weaknesses of common stated-preference methods, and discuss considerations for the future use of these methods. Recent findings: Early literature on patient preferences often mimicked clinical practice, asking whether treatment A is better or worse than treatment B for a patient. Early applications of patient preference methods in rheumatology aimed to value different attributes of treatments, but remained focused on informing clinical questions. Spurred by interest in preferences by regulatory agencies and patient-centeredness throughout the product lifecycle, there are now a wide array of methods available to measure preference. Summary: Although these different preference methods have strengths and weaknesses, they serve to highlight the broad number of questions that could help rheumatology beyond the clinical context. Researchers in rheumatology now have the opportunity to better serve diverse stakeholders by considering how these methods could aid in clinical trial design, regulatory policy, and other elements of the medical product life cycle.